When Randomization Is Not Feasible: The Case of Parenting Skills Programs - Daniela Del Boca; Chiara D. Pronzato; Lucia Schiavon (Institute of Labor Economics (IZA), 2023)
One of the aims of parenting programs is to enhance parental skills and behaviours for the well-being of children. This study examines the effects of the FA.C.E. ("Becoming Educating Communities") program, focusing on parents' use of time with their children. Promoted by the non-profit organization Con I Bambini, FA.C.E. ran for three years, with funding from several Italian philanthropic foundations and the Italian government. Here we evaluate the impact of the second edition of the program on parental perceptions and on children's time use during the 2020/2021 school year. Two obstacles prevented us from implementing randomization, which would have necessitated the randomization of two cohorts of families, with the first commencing the program immediately and the second starting later. The initial challenge arose from the COVID-19 pandemic, which confined people to their homes. It was therefore decided to encourage families to attend in person as often and whenever they could, with no restrictions imposed on their impromptu participation. The second issue stemmed from the randomization used to evaluate the first edition of FA.C.E., which led several families to abandon the program, either because they had wanted to start immediately or because they had not been placed with their family's friends. For the second edition of the program, we collected data from each family before and after their participation in the program and rely on two different empirical strategies to evaluate the program's impact. We also include a test to help determine which is the most reliable estimate.
Keywords: J13; J18; C80; D1; I26; 330; parenting skills; use of time; well-being; policy evaluation; impact evaluation methods; treated-controls model; mixed methods